2011
DOI: 10.1002/chem.201101855
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of Homochiral Homo‐oligomers of Parent cis‐ and trans‐Furanoid‐β‐Amino Acids

Abstract: The synthesis of homochiral homo-oligomers of cis- and trans-3-aminotetrahydrofuran-2-carboxylic acids (parent cis- and trans-furanoid-β-amino acids, referred to as "cis-/trans-FAA") has been carried out to understand their secondary structures and their dependence on the ring heteroatom. The oligomers of two diastereomers have been shown to have a distinct left-handed helicity. The cis-FAA homo-oligomers show a 14-helix structure, in contrast to the homo-oligomers of cis-ACPC, which adopt a sheet like structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 74 publications
(38 reference statements)
5
28
0
2
Order By: Relevance
“…With detailed experimental studies on various fully protected 3-Osulfonyl-furanoses we have established optimum conditions forming key intermediates and derivatives. As described recently (Pandey 2011;Giri 2012), newly synthesized sugar amino acid derivatives including the herein reported Fmoc-X-, key reactions and intermediates of the sterically hindered secondary amines were probed to make successfully -Aaa-tX-Aaa-and -Aaa-tX-tX-Aaatype "inserts" for α/β-chimera peptides. Thus, we have shown that both C-3 epimers of 3-azido-3-deoxy-pentofuranuronic acid, N 3 -RibAFU(ip)-OH (6) and N 3 -XylAFU(ip)-OH (7) are suitable building blocks to be inserted into β/β-oligopeptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With detailed experimental studies on various fully protected 3-Osulfonyl-furanoses we have established optimum conditions forming key intermediates and derivatives. As described recently (Pandey 2011;Giri 2012), newly synthesized sugar amino acid derivatives including the herein reported Fmoc-X-, key reactions and intermediates of the sterically hindered secondary amines were probed to make successfully -Aaa-tX-Aaa-and -Aaa-tX-tX-Aaatype "inserts" for α/β-chimera peptides. Thus, we have shown that both C-3 epimers of 3-azido-3-deoxy-pentofuranuronic acid, N 3 -RibAFU(ip)-OH (6) and N 3 -XylAFU(ip)-OH (7) are suitable building blocks to be inserted into β/β-oligopeptides.…”
Section: Resultsmentioning
confidence: 99%
“…Foldamer synthesis with sterically hindered amines is a challenge and thus, preliminary reaction in optimizing conditions for making short sequences from β-amino acids is a requirement: dimeric, tetrameric and hexameric units form some of them were already studied (Chandrasekhar 2004;Chandrasekhar 2005;Jagannadh 2006;Pandey 2011;Giri 2012). Here we present the synthesis of Nterminal "masked", C-terminal protected -X-X-type β-dipeptide, by coupling N-methylated 3-amino-3-deoxy-ribofuranuronamide (28) with the related 3-azido-3-deoxy-ribofuranuronic acid (6, Scheme 8).…”
Section: Coupling Trans Afu Derivatives Making New β-Peptide Derivatimentioning
confidence: 99%
“…Recently, sugar amino acids (SAA), par-ticularly, fiveor six-membered cyclic amino sugar carbox-ylic acids, appeared as appropriate building blocks for car-bopeptoid foldamers (Herradón and Seebach 1989;Kessler et al 1995;Long et al 1999;Simone et al 2005;Sharma et al 2008Sharma et al , 2011Andreini et al 2009). Numerous furanoid and pyranoid carbohydrate analogs of trans-2-aminocyclo-pentane carboxylic acid (trans-ACPC) and trans-2-amino-cyclohexane carboxylic acid (trans-ACHC) were synthe-sized and built into homo-and heterooligomers to test their self-assembling abilities (Pandey et al 2011;Giri et al 2012;Risseeuw et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Figure 1 provides the secondary structures of some homo-oligomers of β-FAAs. [5] The homo-oligomers of two diastereomeric FAAs have been shown to have distinct lefthanded helicity, in which cis-FAA oligomers VI are characterized by the presence of a 14-helix structure, which is in contrast to the cis-ACPC homo-oligomers II [6] that adopt nary investigation of their solution secondary structures revealed that they are the same as the homo-oligomers of the parent cis-/trans-FAA with the methoxy group only being a spectator substituent. As expected, the folding propensity of the homo-oligomers is not comparable to each other.…”
Section: Introductionmentioning
confidence: 99%